2022
DOI: 10.3758/s13423-022-02136-7
|View full text |Cite
|
Sign up to set email alerts
|

Does bilingualism come with linguistic costs? A meta-analytic review of the bilingual lexical deficit

Abstract: A series of recent studies have shown that the once-assumed cognitive advantage of bilingualism finds little support in the evidence available to date. Surprisingly, however, the view that bilingualism incurs linguistic costs (the so-called lexical deficit) has not yet been subjected to the same degree of scrutiny, despite its centrality for our understanding of the human capacity for language. The current study implemented a comprehensive meta-analysis to address this gap. By analyzing 478 effect sizes from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 176 publications
2
4
0
Order By: Relevance
“…Additionally, we found that at the group level, HL speakers outperformed L2 speakers of each respective language in the same country, supporting findings across linguistic domains that found an advantage for HL speakers over L2 learners in oral production ( Montrul et al, 2008 ; Saadah, 2011 ; Albirini and Benmamoun, 2014 ; Rakhilina et al, 2016 ). Likewise, this finding seems to support the results of the meta-analysis by Bylund et al (2023) , who found an advantage for simultaneous bilinguals (in this case HL speakers, although several of them were, in fact, sequential, although not by a significant number of years) over sequential bilinguals in the L2/HL, but not in the L1/SL. Notably, however, the HL-HEB-US group matched the L2-HEB-IL group on the Hebrew MINT, suggesting that the HL advantage over the L2 learner disappears in an immersive environment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, we found that at the group level, HL speakers outperformed L2 speakers of each respective language in the same country, supporting findings across linguistic domains that found an advantage for HL speakers over L2 learners in oral production ( Montrul et al, 2008 ; Saadah, 2011 ; Albirini and Benmamoun, 2014 ; Rakhilina et al, 2016 ). Likewise, this finding seems to support the results of the meta-analysis by Bylund et al (2023) , who found an advantage for simultaneous bilinguals (in this case HL speakers, although several of them were, in fact, sequential, although not by a significant number of years) over sequential bilinguals in the L2/HL, but not in the L1/SL. Notably, however, the HL-HEB-US group matched the L2-HEB-IL group on the Hebrew MINT, suggesting that the HL advantage over the L2 learner disappears in an immersive environment.…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis of 130 studies found evidence for the bilingual “lexical deficit” ( Bylund et al, 2023 , p. 898) only among sequential bilinguals who learned their L2 later in life, and only in the L2, and not for simultaneous bilinguals or for sequential bilinguals in their L1 ( Bylund et al, 2023 ). Meanwhile, while HL speakers (who can be either simultaneous or early sequential bilinguals) score fairly consistently higher on vocabulary assessments in their dominant SL, usually their L2, than in their HL, their lexical proficiency has been shown to be highly variable (see, for example, Fridman and Meir, 2023a , findings that HL-Hebrew speakers in the US ranged from 15 to 82% accuracy on an HL vocabulary assessment).…”
Section: The Bilingual Lexiconmentioning
confidence: 99%
“…Word learning may be more complex for bilinguals than monolinguals: Consistent with this, some studies reported bilingual children to have a smaller vocabulary than monolingual ones (e.g., De Houwer et al, 2014;Montanari et al, 2018). Nevertheless, more recently, some authors did not find a lexical deficit (i.e., smaller vocabulary and slower word retrieval compared to monolinguals) in balanced bilingual children (e.g., Bylund et al, 2022); others have argued that vocabulary tests were created for testing monolinguals and that they, therefore, do not accurately represent bilinguals' word knowledge (Ehl et al, 2020).…”
Section: Word Learning In Bilingualsmentioning
confidence: 87%
“…First, multilinguals show lower performance in some aspects of language processing (e.g., Bialystok et al, 2009). For example, multilingual children and adults are often found to exhibit smaller vocabularies than monolinguals in each of their languages separately; and especially in their second language (e.g., Bialystok & Luk, 2012;Bylund et al, 2023).…”
Section: Multilingualism and Cognitionmentioning
confidence: 99%
“…Overall, investigating the interplay between autistic traits, bidialectalism, and multilingualism is important because some research suggests that such experiences have overlapping cognitive domains of impact. On the one hand, some evidencethough currently controversial-suggests that bidialectals and multilinguals exhibit, under certain conditions, better non-verbal cognitive processing (e.g., Bialystok & Craik, 2022; though see Paap, 2023) but worse language performance (e.g., Bialystok et al, 2009;Bylund et al, 2023), at least in some respects. On the other hand, ASD, or autistic traits more broadly, are often linked to lower language and non-verbal 7 cognitive performance (e.g., Demetriou et al, 2018;Hoekstra et al, 2009;Marinopoulou et al, 2023;Nader et al, 2016;Stewart et al, 2023).…”
mentioning
confidence: 99%